(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2020)
This article discuss how a border policy of a particular country shaped the economic, political and security of the neigbouring countries. Border in the era of globalization, it is beyond a mere geographical demarcation that separates one country from the other. It occupies a central place in the international, continental and regional economic, political and security discourse. The decision of the Federal Government of Nigeria to close its land borders in August 2019 for economic and security reasons has affected commercial activities and movement of people between the frontiers of Nigeria with Togo, Benin Republic, Cameroon, and Niger Republic. Secondary data were sourced for the analysis and discussion. Hegemonic Stability Theory is adopted as theoretical framework to explain the phenomenon. The results show that the internal affairs of Nigeria become a theme for discussion at the regional economic bloc, Economic Community of West African States. Domestically, Nigerian government has portrayed border closure as one of the best decision to safeguard home industries and farmers from the importation of cheap goods. The paper further found that the border closure has provided Nigeria with an opportunity to compelled its neighbours to set up a joint border security patrol to check the influx of undocumented migrants, illegal selling of weapons, importation contraband products and discontinue the harbouring of terrorist groups in the border communities. However, the border closure led to economic hardship for Nigerians at the border communities and those who engage in cross border trade by rendering them jobless. Therefore, the article concludes that border can be used by an economically strong country to protects its political, economic and security interests. This is evident between Nigeria with its neigbhours when Nigeria shut its land borders because it is stronger than all its entire neighbours; economically and politically as well as military strength. Also, with a population of over 280 million people, it is a huge market in which the neighbours takes advantage of, for trading, labour migration and other commercial activities.